The Voice of Human Ecology in the Novel The Bear (2020) by Andrew Krivak - Annisa Sabrina (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2021)
As a movement that has held an important position in the humanities for the past few decades, eco-criticism or environmental-oriented literature needs to promote a better understanding of nature more broadly. That is, ecocriticism must distinguish itself from writings on the environment in general, namely by presenting a narrative showing that humans need to have a sense of attachment to nature, as well as by presenting a narrative showing that the world of humans and the world of non-humans needs to be positioned equally. In the novel The Bear (2020) by Andrew Krivak, the voice of equality between humans and nature is the dominant issue. Using the human ecology concept from Philip J. Stewart as a key concept, this study aims to describe how human fragility and natural domination presented in the novel The Bear (2020) support the idea of human ecology, as well as how human ecologyvoiced in the novel The Bear (2020) criticizes the view of anthropocentrism which believes that humans are the center of life. This study shows that the voice of human ecology in the novel The Bear (2020) which is presented through human fragility, natural domination, to criticism of the anthropocentrism view offers the idea of a balance between humans and nature. The balance in question is a condition in which humans and nature return to an equal position, where neither one of them is harmed.